2020
DOI: 10.1108/mabr-02-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring seafarers’ welfare under the Maritime Labour Convention: an empirical case study of Greece

Abstract: Purpose This paper aims to examine three of the major issues relating to the welfare of seafarers, including wages, social security benefits and onboard and ashore welfare facilities and services. It is impossible to research all countries here, so this paper selects Greece – which is one of today’s primary shipping countries as for shipowning, as well as for global supply and demand for seafarers – to conduct an empirical case study. Design/methodology/approach Based on the existing knowledge and scholarshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although the number of seafarers recruited from Far Eastern countries, the Indian sub-continent, and Eastern Europe is increasing, the share of Chinese seafarers in the international seafarer labour market remains stable at around 8% (Nguyen et al, 2014;Thai et al, 2013). This condition causes a scarcity of seafarers both in terms of quality and quantity, which ultimately increases seafarers' salary levels and encourages market players to recruit seafarers from "third world" countries (Lobrigo & Pawlik, 2015;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of seafarers recruited from Far Eastern countries, the Indian sub-continent, and Eastern Europe is increasing, the share of Chinese seafarers in the international seafarer labour market remains stable at around 8% (Nguyen et al, 2014;Thai et al, 2013). This condition causes a scarcity of seafarers both in terms of quality and quantity, which ultimately increases seafarers' salary levels and encourages market players to recruit seafarers from "third world" countries (Lobrigo & Pawlik, 2015;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This technology, which is also known as "shore-side power", "on-shore power supply", "alternative maritime power", and "cold-ironing", reduces ship emissions while berthing, to as low as 5% of the original level, by moving the power production from dirty onboard sources to greener and more efficient large-scale power stations [10,11]. In addition to the environmental benefits, the application of SP, also, improves the welfare of seafarers [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information of the case study result. ,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66, 67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91 Routes that finally adopt SP 1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35, 36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,53,54,55,56,57,58,59,60,62,63,64,65,66,67, 68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85…”
mentioning
confidence: 99%
“…The shipping company's primary safety goal is to minimize the risk to property (ships, containers, and machinery), personnel (employees, crew, and passengers) and the environment (air, water, noise) (Chang et al, 2019). In order to improve the safety of shipping and its environment, the International Maritime Organization (IMO) has developed a number of international conventions related to the safety of commercial vessels and maritime navigation, such as the "International Safety Management Code (ISM Code)"; "International Convention on Standards of Training, Certification and Watchkeeping for Seafarers (STCW)"; "International Convention for the Safety of Life at Sea (SOLAS)", "International Convention for the Prevention of Pollution from Ships (MARPOL)", and "Maritime Labor Convention (MLC)" (Zhang et al, 2020). However, in spite of the IMO having several regulations on maritime safety, maritime accidents still occur frequently.…”
Section: Introductionmentioning
confidence: 99%
“…applicability might be questioned as it is unclear whether social exchange relationships and safety citizenship behavior will lead to a decrease in ship accidents. Related research has found that safety behavior is significantly related to accidents(Hofmann and Morgeson, 1999;Zhang et al, 2020). Third, a potential limitation is that it might be argued that the measurement of LMX, TMX, and safety citizenship behavior is affected by common method bias.…”
mentioning
confidence: 99%